University Students’ Engagement with Devices and Technology: A Comparison of Pre- and Post-COVID-19 Student Use - Cradduck, Lucy; Gregory, Mark A.; Campbell, Leith H. (Journal of Telecommunications and the Digital Economy, 2022)
In this paper, through the replication of a pre-COVID-19 research project, we seek to test and compare first-year Australian university students’ study and private uses of technology; compare the desires and capacities of different cohorts (Law and Justice vs Engineering) for technology use; and identify any impacts arising from COVID-19 to their learning experiences. Quantitative and qualitative data, collected by an online questionnaire, identified that, while some participants had more experience with different technologies, there were limited differences between the cohorts’ willingness to use, and their use of, technology for study purposes. Concerns expressed by participants related to where, when, and for what purpose technology was used. Participants all had access to a smart phone, and almost all used a laptop for study purposes. The results suggest the combination of online or pre-recorded lectures and synchronous (either face-to-face or online) tutorials was the most favoured option. While participants were comfortable with the use of technology in teaching and learning, they were wary about using such tools for private communications; however, Zoom and Microsoft Teams, appeared to be in common use. The results confirm the need for a broader and more in-depth understanding of students’ technology uses, needs, and desires.